AeroDima: a cheetah-inspired aerodynamic tail for rapid manoeuvrability - Bright, Daryn (Department of Electrical Engineering, 2025)
The cheetah, the fastest land animal has been hypothesised to use its tail for manoeuvrability and has been the source for many bio-inspired robotic tails. However, the use of a lightweight tail to achieve the same effects has not be studied. This paper goes into the study of using a lightweight, aerodynamic tail to increase manoeuvrability on a wheeled platform, AeroDima. This is achieved by studying the aerodynamics of a cheetah's tail in a wind tunnel to develop a quasi-steady state model. A bio-inspired aerodynamic tail was then designed to maximise drag forces. This bio-inspired tail was also studied in a wind tunnel and compared to the cheetah tail's model. The tail required a platform to operate on, so AeroDima was designed and manufactured. The tail, designed to be a 3DOF underactuated system, was designed to test the effects of the tail on high-speed manoeuvres through a roll motion swing of the tail. The system was tested both in simulation and physical experiments. The simulation, developed with MATLAB's Simscape Multibody toolbox, was designed to be a comprehensive model of AeroDima.